Expression and functional analysis of Nr2e3, a photoreceptor-specific nuclear receptor, suggest common mechanisms in retinal development between avians and mammals - Kobayashi, Mime (Springer-Verlag, 2008)
The photoreceptor-specific nuclear receptor (PNR; Nr2e3) is a transcription factor important for retinal development. We report here the identification and expression analysis of the avian Nr2e3. Nr2e3 mRNA is expressed in the photoreceptor layer of the neural retina during early stages of chick embryogenesis. Its temporal expression is distinct from that of a related nuclear receptor, Tlx. Chick Nr2e3 recognizes and binds to the same target DNA sequence as its vertebrate orthologs. Functional assays revealed that chick Nr2e3 acts as a transcriptional repressor. Our results suggest that Nr2e3 plays a common role in retinal development in vertebrates.